Implementation of Arabic Week Program to Improve Speaking Skills at Darussalam Gontor Modern Islamic Institution 1st/ تنفيذ برنامج الأسبوع العربي لترقية مهارة الكلام في معهد دار السلام كونتور الإسلامي الحديث الأول - Nur Cholis Irvansyah; Nurul Ainiy; Zakiyah Arifa (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2022)
Learning Arabic that takes place only in the classroom is not enough to achieve maximum educational goals. Therefore, Arabic week programs offered by formal and informal institutions began to emerge. One of them is an Arabic week program implemented by Darussalam Modern Islamic Institution First for Male in Ponorogo to improve students' speaking skills. This research aims to study 1) the process of implementing the Arabic week program, 2) the drivers and implementers of the Arabic week program at Darussalam Modern Islamic Institution, 3) the role of the Arabic week program on students' speaking skills, and 4) the factors that influence Arabic week program implementation. This research uses a qualitative approach with the type of case study. The data sources are teachers, supervisors, students, documents, conditions, and phenomena in the research field. Primary data is a collection of information that includes words, actions, and facts, while secondary data is information from other references. Data collection methods are observation, interviews, and documentation. Data were analyzed using data reduction, data classification, data presentation, and concluding. Based on the results of the study, it can be concluded that the implementation of the Arabic Week Program consistently and regularly in this school can improve students' Arabic skills. This success is supported by the efforts of language drivers as program organizers and implementers. With good implementation management, this program can achieve its goal of improving students' ability to speak Arabic fluently. Various factors have contributed to the success of this program, one of which is a good role and example of the administrators and teachers in empowering the Arabic Week Program to students, besides that students live in an orderly environment and strict language discipline. إن تعلم اللغة العربية الذي يتم فقط في الفصول الدراسية يُعد غير كافٍ لتحقيق الأهداف التعليمية بشكل أقصى حد. لذلك، بدأت تظهر البرامج اللغوية العربية تقدمها المؤسسات الرسمية وغير الرسمية. وأحدها برنامج الأسبوع العربي الذي يقدمها معهد دار السلام كونتور الحديث للبنين الأول بمدينة فونوروكو لترقية مهارة الكلام لدى الطلاب. ويهدف هذا البحث إلى دراسة 1) عملية تنفيذ برنامج الأسبوع العربي، و2) المحرك في تنفيذ برنامج الأسبوع العربي في معهد دار السلام كونتور، و3) دور برنامج الأسبوع العربي على مهارة الكلام لدى الطلاب، و4) العوامل التي تؤثر في تنفيذ برنامج الأسبوع العربي. يستخدم هذا البحث المدخل الكيفي بنوع البحث دراسة حالة. ومصادر البيانات هي المعلم والمشرف والطلاب والوثائق والأحوال والظواهر الموجودة في ميدان البحث. والبيانات الأساسية هي مجموعة من المعلومات التي تشمل على الأقوال والأفعال والوقائع، والبيانات الثانوية وهي معلومات من مراجع أخرى. وطريقة جمع البيانات هي الملاحظة والمقابلة والتوثيق. وتم تحليل البيانات بالخطوات تقليل البيانات، وتصنيف البيانات، وعرض البيانات، والاستنتاج. بناء على نتائج البحث، يستنتج أنه يمكن أن يؤدي تنفيذ برنامج الأسبوع العربي بشكل مستمر ومنتظم في معهد دار السلام كونتور الإسلامي الحديث الأول للبنين إلى ترقية مهارات الطلاب في اللغة العربية. هذا النجاح مدعوم بجهود محركي اللغة كمنظمين ومنفذين للبرنامج. من خلال إدارة التنفيذ الجيدة، يمكن لهذا البرنامج أن يحقق هدفه المتمثل في تحسين قدرة الطلاب على التحدث باللغة العربية بطلاقة. ساهمت عوامل مختلفة في نجاح هذا البرنامج، أحدها مثال جيد من المدير والمعلمين في تمكين برنامج الأسبوع العربي للطلاب، إلى جانب أن الطلاب يعيشون في بيئة منظمة وانضباط لغوي صارم.